Does government spending crowd out voluntary labor and donations? - Julia Bredtmann; Fernanda Martínez Flores (IZA World of Labor, 2023)
Private charitable contributions play an essential role in most economies. From a policy perspective, there is concern that comprehensive government spending might crowd out private charitable donations. If perfect crowding out occurs, then every dollar spent by the government will lead to a one-for-one decrease in private spending, leaving the total level of welfare unaltered. Understanding the magnitude and the causes of crowding out is crucial from a policy perspective, as crowding out represents a hidden cost to public spending and can thus have significant consequences for government policies toward public welfare provision.
Keywords: H51; 31; H11; 330; private philanthropy; time and money donations; government spending; crowding out